The influence of caffeinated and non-caffeinated multi-ingredient pre-workout supplements on resistance exercise performance and subjective outcomes. Issue 1 (31st December 2022) - Stratton, Matthew T.; Siedler, Madelin R.; Harty, Patrick S.; Rodriguez, Christian; Boykin, Jake R.; Green, Jacob J.; Keith, Dale S.; White, Sarah J.; DeHaven, Brielle; Williams, Abegale D.; Tinsley, Grant M.
ABSTRACT: Background: There is substantial consumer and practitioner interest in an emerging supplement class known as multi-ingredient pre-workout supplements (MIPS), largely due to their prevalence in resistance training communities as well as research findings demonstrating the ergogenic impact of caffeine on muscular performance. However, limited research has examined the potential efficacy of non-caffeinated MIPS, despite their growing popularity among those who are caffeine-sensitive or who train later in the day. Methods: Twenty-four resistance-trained college-aged males (n = 12) and females (n = 12) completed three visits in which they ingested either a caffeinated MIPS (C), an otherwise identical non-caffeinated MIPS (NC), or placebo in a double-blind, counterbalanced, crossover fashion. Squat isometric peak force (PFiso ), rate of force development (RFD), and isokinetic performance were assessed. Upper and lower body maximal muscular strength and endurance were evaluated using the bench press and leg press, respectively. Visual analog scales for energy, focus, and fatigue were completed five times throughout the testing protocol. The effects of supplementation and biological sex on all variables were examined using linear mixed effects models. Results: Significantly greater PFiso was observed in both C ( b : 0.36 transformed units [0.09, 0.62]) and NC ( b : 0.32 transformed units [95% CI: 0.05, 0.58]) conditions, relative to placebo. Early RFD (RFD50 ) may have been higher with supplementation, particularly in females, with no effects for late RFD (RFD200 ) or peak RFD. In addition, increases in subjective energy after supplement ingestion were noted for C, but not NC. No effects of supplementation on traditional resistance exercise performance or isokinetic squat performance were observed, other than a lower leg press one-repetition maximum for males in the NC condition. Conclusions: These data indicate that acute ingestion of either a caffeinated or non-caffeinated pre-workout formulation improved maximal force production during an isometric squat test but did not provide additional benefit to leg press, bench press, or isokinetic squat performance over placebo, within the context of a laboratory environment. The consumption of a caffeinated, but not non-caffeinated, MIPS increased subjective ratings of energy over placebo when assessed as part of a testing battery.